The impact of task-sharing scalable mental health interventions on non-specialist providers: a scoping review - Manaswi Sangraula; Josheka Chauhan; Chynere Best; Caroline McEneaney; Cheenar Shah; Adam D. Brown; Brandon A. Kohrt (Cambridge Prisms: Global Mental Health)
Task-sharing approaches that train non-specialist providers (NSPs), people without specialized clinical training, are increasingly utilized to address the global mental health treatment gap. This review consolidates findings from peer reviewed articles on the impact of task-sharing mental health interventions on NSPs at the individual, family and community level. Studies that highlighted facilitators, barriers and recommendations for improving the experiences of NSPs were also included in the review. Fifteen studies, conducted across eight countries, met the inclusion criteria. Seven studies were conducted in Sub-Saharan Africa, six in South and Southeast Asia and two studies were conducted in high-income countries in Europe. Benefits for NSPs included personal application of mental health skills, elevated community status and increased social networks. Challenges include burnout, lack of career progression and difficult workplace environments. Findings indicate that while there were many positive impacts associated with NSPs’ work, challenges need to be addressed. Safety and harassment issues reported by female NSPs are especially urgent. Supervision, certifications, increased salaries and job stability were also recognized as significant opportunities. We recommend future intervention studies to collect data on the impact of intervention delivery on NSPs. Research is also needed on the impact of various supervision and health systems strategies on NSPs.